2006
DOI: 10.1128/jb.00810-06
|View full text |Cite|
|
Sign up to set email alerts
|

The Methanosarcina barkeri Genome: Comparative Analysis with Methanosarcina acetivorans and Methanosarcina mazei Reveals Extensive Rearrangement within Methanosarcinal Genomes

Abstract: We report here a comparative analysis of the genome sequence of Methanosarcina barkeri with those of Methanosarcina acetivorans and Methanosarcina mazei. The genome of M. barkeri is distinguished by having an organization that is well conserved with respect to the other Methanosarcina spp. in the region proximal to the origin of replication, with interspecies gene similarities as high as 95%. However, it is disordered and marked by increased transposase frequency and decreased gene synteny and gene density in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
114
1
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 159 publications
(121 citation statements)
references
References 54 publications
4
114
1
2
Order By: Relevance
“…To remove contaminating chromosomal DNA, the RNA preparation was digested with TURBO DNA-free (Ambion, Austin, TX). This RNA preparation (5 mg) was then treated with 20 units of tobacco acid pyrophosphatase (Maeder et al, 2006) (Epicentre, Madison, WI) for 1 h at 37°C in the presence of 80 units of RNasin (Promega, Madison, WI). A negative control was included where the tobacco acid pyrophosphatase was replaced with RNase-free water (TAP -control).…”
Section: Determination Of Tssmentioning
confidence: 99%
See 1 more Smart Citation
“…To remove contaminating chromosomal DNA, the RNA preparation was digested with TURBO DNA-free (Ambion, Austin, TX). This RNA preparation (5 mg) was then treated with 20 units of tobacco acid pyrophosphatase (Maeder et al, 2006) (Epicentre, Madison, WI) for 1 h at 37°C in the presence of 80 units of RNasin (Promega, Madison, WI). A negative control was included where the tobacco acid pyrophosphatase was replaced with RNase-free water (TAP -control).…”
Section: Determination Of Tssmentioning
confidence: 99%
“…Although homologues for the MtsA/B system are present in M. barkeri Fusaro and Methanosarcina mazei Gö1, they are absent in M. acetivorans C2A. Therefore, this organism must use novel enzymes for the utilization/ production of DMS (Deppenmeier et al, 2002;Galagan et al, 2002;Maeder et al, 2006). Because the production of DMS occurs concomitantly with the upregulation of MA0859, MA4384 and MA4558 during growth on CO (Rother et al, 2007;Moran et al, 2008), these open reading frames (ORFs) might encode DMS-specific methyltransferases.…”
Section: Introductionmentioning
confidence: 99%
“…Horizontal transfer in the opposite direction appears to have occurred in the huge genome of Methanosarcina acetivorans [13], including the only archaean genes for homologues of thermolysin (peptidase family M4) and clostripain (peptidase family C11): both peptidase families are otherwise only known from bacteria. The closely related M. barkeri is equally a 'kleptomaniac' for foreign genes [14], but this genome contains a real surprise. Multicellular eukaryotes have to kill their own cells during development and to recycle tissues.…”
mentioning
confidence: 99%
“…For instance, comparative genomics of M. barkeri Fursaro, M. acetivorans C16 and M. mazei Gö1 revealed that large fluctuations in genome size (up to~1.7 Mb) were likely caused by gene insertions, localized inversions and transpositions (Maeder et al, 2006). In addition, gene gain from bacterial taxa is common in at least some Methanosarcina spp.…”
Section: Introductionmentioning
confidence: 99%